Systems analysis and design - Kendall, Kenneth E. (Pearson/Prentice Hall, 2008)
Dynamic, comprehensive coverage makes this the perfect book on systems analysis and design, with a reader-friendly presentation of development, methods, tools, and techniques. A variety of review questions and problems, an ongoing case study, and an Internet-based case study offer learners an understandable and motivating look at the SAD field. For production supervisors and other business personnel in similar positions who want a working knowledge–without the in-depth command–of information systems.